metaphor and their transformations in surrealist painting (Al-Academy, 2024)
The problem of research tagged: (metaphor and its transformations in the surreal drawing) dealt with the nature of the concept of metaphor and the mechanisms of its work in the contemporary global achievement. The research came in four chapters: The first chapter was concerned with the systematic framework for the research represented by the problem of the research, as it was manifested through this study by metaphor and its transformations, which were associated with the Surreal drawing papers in Europe. The goal of the study has been crystallized with the following:Exposing metaphor and its transformations in the visual system of the surreal drawing.As for the limits of the research, I was interested in analyzing video models, for the surreal drawing for the period from (1922-1938)As for the second chapter, which is the theoretical framework, it contained three investigations that dealt with the first topic: metaphor: the concept and meaning in the visual field.As for the second topic: it dealt with the transformations of showing techniques in formation, and the third topic: I meant the study of the transformation in art between concepts and facts.As for the third chapter, it is concerned with research procedures represented by the metaphor applications in the surreal drawing, then after that it included the identification of the research community and its adult eye (4) models, then the research tool and the analysis of the sample.As for the fourth chapter, it included the results of the research, conclusions, recommendations and proposals. The researcher has reached a number of results in response to the goals of the research, including:1- The concept of technology in the surreal drawing has been a metaphor for the immediate moments that break the perception, in light of the references and displacements that are emanating on imagination.2- The optical surface is influenced by activating the movement of the calligraphy, and by means of the indicative action, in a way that achieves a visual displacement regarding the mock metaphor, which makes it lose its objective prayers.3- The removal of visual systems from its objective circle by activating forms and in an automatic dynamic way, embodies the semantic discourse, which often gives its ambiguity an intense poetic dialogue, which enhances the role of the legendary reference.The researcher reached a set of conclusions and then the list of sources and references.